Pengaruh Keputusan Investasi, Struktur Modal Dan Kebijakan Dividen Terhadap Nilai Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Yasmin, Salma Alivia; Ahyar, Muhammad; Santoso, Budi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study aims to analyze the effect of investment decisions, capital structure and dividend policy on the value of LQ45 companies listed on the Indonesia Stock Exchange in 2019-2023. This research is a causal associative research (cause and effect) with a quantitative approach. In this study, the sample selection was carried out by purposive sampling method. Based on the predetermined criteria, a sample of 19 companies from 45 companies was obtained. In this study, a panel data regression model was applied with the Fixed Effect Model (FEM) approach and using the Eviews 12 program. The results showed that investment decisions have a positive and significant effect on firm value, capital structure has a negative but insignificant effect on firm value, and dividend policy has a negative but insignificant effect on firm value. From the results of this study, it is hoped that companies can be maximized in managing investment decisions, capital structure, and dividend policy in an effort to increase firm value, especially LQ45 companies listed on the Indonesia Stock Exchange in 2019-2023.